2012
DOI: 10.5533/dst-2177-8264-201224303
|View full text |Cite
|
Sign up to set email alerts
|

Perfil CitoPatológiCo de Mulheresatendidas nas unidades BásiCas do MuniCíPio de uruguaiana, rs

Abstract: Introdução: o câncer do colo de útero tem sido apontado como o terceiro tipo de câncer mais comum entre as mulheres e sua relação com a infecção por papilomavírus humano (HPV) é bem estabelecida. objetivo: conhecer o perfil citopatológico de mulheres atendidas nas Unidades Básicas de Saúde do município de Uruguaiana, RS. Métodos: análise retrospectiva de corte transversal e descritivo dos laudos de exames citopatológicos de pacientes que realizaram a citopatologia ginecológica (Papanicolaou) e respectivos pron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
5
0
2
Order By: Relevance
“…(26) . Outros autores corroboraram com esse resultado, que apesar de ser um dado considerável encontra-se dentro do esperado que é até 5% dos exames (27)(28)(29) . No Pará 1,45%…”
Section: Introductionunclassified
“…(26) . Outros autores corroboraram com esse resultado, que apesar de ser um dado considerável encontra-se dentro do esperado que é até 5% dos exames (27)(28)(29) . No Pará 1,45%…”
Section: Introductionunclassified
“…6 In the present study, the prevalence of CC cases was found to be concentrated in the age range of 37 to 57 years old, with a total of three cases. Diverging from the findings found in the research by Ströher and his colleagues, 12 where the majority of women were younger than 25 years. However, this picture has been gradually changing, and the appearance of precursor lesions is occurring earlier, also due to the early initiation of sexual activity and its association with other risk factors.…”
Section: Discussionmentioning
confidence: 65%
“…However, this picture has been gradually changing, and the appearance of precursor lesions is occurring earlier, also due to the early initiation of sexual activity and its association with other risk factors. 12 Regarding the diagnosis of ASC US or atypicals of undetermined significance in glandular cells, possibly not neoplastic, it is recommended not to exceed 5% of all diagnoses in the same laboratory. 21 For Ströher et al, 12 ASC-US is the most found in examinations processed in the cytology laboratories.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations